Review: dermatitis herpetiformis - Fernanda Berti Rocha Mendes; Adaucto Hissa-Elian; Marilda Aparecida Milanez Morgado de Abreu; Virgínica Scaff Gonçalves (Sociedade Brasileira de Dermatologia, 2013)
Dermatitis herpetiformis (DH) or Duhring-Brocq disease is a chronic bullous disease characterized by intense itching and burning sensation in the erythematous papules and urticarial plaques, grouped vesicles with centrifuge growth, and tense blisters. There is an association with the genotypes HLA DR3, HLA DQw2, found in 80-90% of cases. It is an IgA-mediated cutaneous disease, with immunoglobulin A deposits appearing in a granular pattern at the top of the dermal papilla in the sublamina densa area of the basement membrane, which is present both in affected skin and healthy skin. The same protein IgA1 with J chain is found in the small intestinal mucosa in patients with adult celiac disease, suggesting a strong association with DH. Specific antibodies such as antiendomysium, antireticulina, antigliadin and, recently identified, the epidermal and tissue transglutaminase subtypes, as well as increased zonulin production, are common to both conditions, along with gluten-sensitive enteropathy and DH. Autoimmune diseases present higher levels of prevalence, such as thyroid (5-11%), pernicious anemia (1-3%), type 1 diabetes (1-2%) and collagen tissue disease. The chosen treatment is dapsone and a gluten-free diet.